Clinical and therapeutic characteristics of patients with a schizotypal disorder with obsessive-compulsive symptoms - Chelyadyn Юлія; Dzeruzhinskaya Наталія (Psychosomatic Medicine and General Practice, 2022)
Introduction. The prevalence of obsessive-compulsive symptoms in modern conditions of high stress and the lack of detailed recommendations for this category of patients determine the relevance of this publication. The emergence of suffering at a young age forms insufficiently adaptive behaviors and complicates the socialization of such persons. And the emergence of these symptoms within different etiological disorders requires the development of differentiated diagnostic and therapeutic approaches. Materials and methods. The study involved 69 outpatients with leading obsessive-compulsive disorder within schizotypal disorder (F21). The following methods were used: clinical-psychopathological, psychodiagnostic, clinical-follow-up and mathematical statistics. Patients were examined using psychodiagnostic techniques: clinical scale of obsessions and Yel-Brown compulsions (Y-BOCS - Obsessive-compulsive Scale); hospital anxiety and depression scale (HADS); quality of life scale (Chaban OS, 2008); multidimensional scale of perception of social support ("MSPSS" D. Zimet); questionnaire "Lifestyle Index" ("LSI" by R. Plutchik - G. Kellerman - H. R. Conte), method "Psychological diagnosis of coping behavior strategy" by R. Lazarus. Results. The clinical typology of these symptoms: type of avoidance, type of ambivalence and type of accumulation was studied by processing the clinical scale of obsessions and Yel-Brown compulsions (Y-BOCS) in patients with schizotypal disorder (F21). It was found that these symptoms were accompanied by anxiety and depressive symptoms only at the subclinical level, which indicates a lack of criticism of one’s condition. In patients with the leading obsessive-compulsive symptoms in schizotypal disorder, not quite mature variants of the protective structure are actualized, namely, substitution (62.3%), displacement (60.9%), regression (58%) and denial (26.1%). The leading coping strategies of such individuals are self-control (73.9%) and escape-avoidance (55.1%), which differs significantly from the strategies more often used by patients with ACS at the neurotic level. We have proposed a program of comprehensive treatment of this group of patients. Patients were divided into 2 groups, the first of which received a combined (differentiated psychopharmacological interventions and psychotherapy) option of therapy, and the second – only differentiated psychopharmacotherapy. The psychotherapeutic formulation was determined by different focus targets depending on the type of obsessive-compulsive symptoms and consisted of a combination of techniques of cognitive-behavioral therapy (CBT) and gestalt therapy (GT). The results of the follow-up study indicate the effective impact of the developed treatment and rehabilitation program on all components of the mental state and social functioning of patients with all types of obsessive-compulsive symptoms of subpsychotic level. Conclusions. The leading types of ACS in schizotypal disorder and features of psychosocial functioning in patients have been identified, which allowed to create a differentiated approach to the formation of a program of their comprehensive treatment and rehabilitation. Such persons need mandatory psychopharmacotherapy and differentiated psychotherapeutic intervention. The application of the program made it possible to improve the mental state and quality of life and achieve the optimal level of adaptation of patients in various spheres of life, increase periods of remission and prevent recurrence of the disorder.